1992
DOI: 10.1177/096032719201100212
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Cyclophosphamide and Dexamethasone in Paraquat Poisoning: A Prospective Study

Abstract: Between March 1986 and March 1988, 47 consecutive patients, whose paraquat intoxication was confirmed by urine testing, were enrolled in a prospective study on the treatment of paraquat poisoning. Fourteen received a standard treatment regimen consisting of fluid replacement and oral absorbents, and 33 received high-dose cyclophosphamide and dexamethasone, in addition to standard therapy. The case fatality rate in both treatment groups (63 and 61%) was similar. In addition, all 26 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 11 publications
1
44
0
Order By: Relevance
“…However, that study did not include a control group, and few patients with PQ detected in the plasma or urine were examined [4]. A subsequent controlled study [5] did not demonstrate efficacy of the above treatment. Other studies [6,7] have generally indicated that initial simultaneous pulse therapy with CP for 2 days and methylprednisolone (MP) for 3 days followed by DEX for 14 days may be effective in treating patients with moderate to severe PQ intoxication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, that study did not include a control group, and few patients with PQ detected in the plasma or urine were examined [4]. A subsequent controlled study [5] did not demonstrate efficacy of the above treatment. Other studies [6,7] have generally indicated that initial simultaneous pulse therapy with CP for 2 days and methylprednisolone (MP) for 3 days followed by DEX for 14 days may be effective in treating patients with moderate to severe PQ intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, thousands of people die of PQ intoxication every year in the developing world [3], creating an imperative to find an effective treatment. To date, many therapeutic methods developed to treat PQ intoxication have shown poor efficacy [1,2], with only a few treatments demonstrating possible effectiveness [4][5][6][7][8][9][10]. High-dose cyclophosphamide (CP) and dexamethasone (DEX) injected intravenously for 14 days resulted in a 75% survival rate in patients with PQ intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Although high doses of cyclophosphamide and Dexamethasone treatments, including intravenous cyclophosphamide (5 mg/kg/d) and dexamethasone (24 mg/d) for 14 days have been correlated with 75% survival rate after poisoning, 13 a subsequent study did not demonstrate the usefulness of this approach. 14 A report demonstrated that pulse therapy with cyclophosphamide and methyl prednisolone (MP) might be effective in preventing respiratory failure and reducing mortality in patients with moderate to severe poisoning. 15 Pulse therapy with MP is known as a strong antiinflammatory treatment in clinical practice, suppressing ROS production by neutrophils and macrophages, and in the arachidonic acid cascade.…”
Section: Resultsmentioning
confidence: 99%
“…[20] At the same time Perriens et al in another RCT showed no difference in survival benefit in those received supportive therapy or immunosuppressants. [21] Severity of poisoning is graded as mild, moderate to severe and fulminant retrospectively, usually reflecting the amount of poison ingested. In fulminant cases, death occurs in first week, aggressive therapies becoming futile.…”
Section: Discussionmentioning
confidence: 99%